2016
DOI: 10.3758/s13423-016-1012-y
|View full text |Cite
|
Sign up to set email alerts
|

Rule abstraction, model-based choice, and cognitive reflection

Abstract: Numerous tasks in learning and cognition have demonstrated differences in response patterns that may reflect the operation of two distinct systems. For example, causal and reinforcement learning tasks each show responding that considers abstract structure as well as responding based on simple associations. Nevertheless, there has been little attempt to verify whether these tasks are measuring related processes. The current study therefore investigated the relationship between rule- and feature-based generaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…There is now evidence from a range of studies that this eliminative inferential account fails to capture many of the properties of the effect and makes corollary predictions Don, Goldwater, Otto, & Livesey, 2016;Shanks & Darby, 1998;Wills, Graham, Koh, McLaren & Rolland, 2011). This may be the reason why both learning models do a less than impressive job of capturing the pattern of choice data in its entirety.…”
Section: Rule Based-processes In the Inverse Base-rate Effectmentioning
confidence: 99%
“…There is now evidence from a range of studies that this eliminative inferential account fails to capture many of the properties of the effect and makes corollary predictions Don, Goldwater, Otto, & Livesey, 2016;Shanks & Darby, 1998;Wills, Graham, Koh, McLaren & Rolland, 2011). This may be the reason why both learning models do a less than impressive job of capturing the pattern of choice data in its entirety.…”
Section: Rule Based-processes In the Inverse Base-rate Effectmentioning
confidence: 99%
“…This difference in the response patterns between groups was not attributable to differences in learning efficiency, indicating that the result was not simply due to differences in learned associations or selective attention. Second, the researchers classified participants as either rule-based or featurebased, according to their generalization performance in a separate patterning task, in which rule transfer is associated with higher working memory capacity (Wills, Barrasin, & McLaren, 2011), greater cognitive reflection, and more strategic Bmodel-based^choices in reinforcement learning (Don, Goldwater, Otto, & Livesey, 2016). Only those participants who were able to extract and apply an abstract rule in the patterning task exhibited an inverse base-rate effect.…”
Section: Inferential Explanationsmentioning
confidence: 99%
“…Cobos et al (2016) showed the same is true for humans when using a cued-response priming task, whereas verbal ratings were consistent with rule-based generalization. Furthermore, the use of rule-based generalization has been shown to be related to working memory, cognitive reflection, and strategic model-based choice in other instrumental learning tasks (Wills et al, 2011a,b; Don et al, 2015, 2016). However, as with the Perruchet effect, researchers have not yet explored whether these competing forms of generalization have an impact on the strength of future learning.…”
Section: Issues Limitations and Future Directionsmentioning
confidence: 99%